PENYIDIKAN TINDAK PIDANA PENIPUAN WARKAT BANK BERUPA CEK KOSONG DI KEPOLISIAN DAERAH RIAU - Sepria Amnur; Mexsasai Indra; Erdiansyah ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2017)
The use of checks as a means of payment in Indonesia, especially Riau Province still often cause problems, especially about the blank checks that cause harm to the recipient. Issuance of a blank check is qualified as a criminal act of banknote fraud in the form of a blank check, as provided for in Article 378 of the Criminal Code. Marakya bank crime crime in the form of blank checks that occurred in Riau Province is inseparable from the investigation process that has not been optimal. Investigations that have not been optimal in law enforcement of bank criminal acts in the form of blank checks in the Riau Regional Police cause not materialized legal certainty. Therefore, the investigation of banknotes crime in the form of blank checks by the Riau Police Investigators should be optimized in order to realize legal certainty. The purpose of writing this thesis, namely: First, To find out the investigation of criminal acts fraudulent bank in the form of blank checks in the Riau Regional Police. Secondly, to find out whether the proof of criminal act of bank warning fraud in the form of blank checks in Riau Regional Police requires expert information. This type of research can be categorized in the type of sociological research. The research location is Riau Regional Police. Sources of data used are primary data and secondary data. Data collection techniques are interviews and literature studies using deductive methods that draw conclusions from things that are general to things that are special. From the result of the research, there are two main points that can be concluded. Firstly, the investigation of criminal act of bank warning fraud in the form of blank checks at Riau Regional Police has not been optimally proven by the high number of fraud checks and the delay or unfinished professional and proportional investigation process, The lack of optimal investigation due to obstacles, including limited investigation personnel, lack of operational budgets, lack of expert investigators in handling cases of fraud checks, geographical circumstances with the potential for occurrence of crime and minimal witnesses. Secondly, the information of legal experts in the proof of criminal acts of bank warning fraud in the form of blank checks at the Riau Regional Police is still needed in supporting the investigation process due to the lack of evidence ie the minimal witnesses and the lack of expert police in handling the case of the crime of blank check. The effort to overcome the obstacle of investigation of criminal acts of bank fraud in the form of blank checks in Riau Regional Police is to make strict action against every crime that happened, build partnership with other institution (stakeholder) especially banking party and also need the increase of number of investigator personnel, Enhancement of investigator capability through special training in banking. Keywords: Investigation - Fraud Crime - Bank Clips in the Form of Empty Check